2017
DOI: 10.2147/dddt.s131582
|View full text |Cite
|
Sign up to set email alerts
|

Anti-platelet effects of anti-glaucomatous eye drops: an in vitro study on human platelets

Abstract: PurposeAltered platelet aggregability has been implicated in the pathogenesis of glaucoma. This study aims to investigate the anti-platelet potential of intraocular pressure lowering drops, with the possibility of establishing it as an additional mechanism of anti-glaucomatous action.Materials and methodsThe anti-aggregating effects of a series of anti-glaucomatous eye drops were determined on human platelets in the platelet aggregation model, using four known aggregating factors (platelet activating factor [P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Maric et al ( 12 ) found higher MPV levels and nailfold capillary morphological vascular changes in patients with exfoliative glaucoma. Antiplatelet effect of antiglaucomatous eye drops was reported ( 13 ). In a word, altered platelet aggregability may trigger microthrombosis of the retinal capillaries and the short ciliary arteries, which result in vascular damage and generate defects in the microcirculation of the optic nerve head.…”
Section: Discussionmentioning
confidence: 99%
“…Maric et al ( 12 ) found higher MPV levels and nailfold capillary morphological vascular changes in patients with exfoliative glaucoma. Antiplatelet effect of antiglaucomatous eye drops was reported ( 13 ). In a word, altered platelet aggregability may trigger microthrombosis of the retinal capillaries and the short ciliary arteries, which result in vascular damage and generate defects in the microcirculation of the optic nerve head.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that application of synthetic Ab induces significant RGC apoptosis in vivo, while anti-Ab treatment was effective in the prevention of RGC apoptosis in glaucoma patients (17,(47)(48)(49)(50)(51). Additionally, some anti-glaucoma medicines have apparent anti-platelet effects, suggesting that platelets participate in glaucoma development (52).…”
Section: Ab Peptide Accumulation Is Associated With a Variety Of Diseasesmentioning
confidence: 99%
“…Ингибиторы карбоангидразы бринзоламид и дорзоламид и β-адреноблокаторы бетаксолол и тимолол оказывают антитромбоцитарный эффект и ингибируют агрегацию тромбоцитов, в отличие от α2-адреномиметиков (бримонидин), не обладающих таким действием [16]. Фармакологический эффект дорзоламида обратно пропорционален центральной толщине роговицы [17].…”
Section: патогенетические основы побочного действия активных веществ unclassified